Mechanistic Explanation for Actions Based on the Joint Construction of Goals and Means - Prudkov, Pavel N.; Rodina, Olga N. (British Journal of Healthcare and Medical Research, 2025)
People describe and explain everyday behavior and cognition in terms of actions, that are goal-directed processes. There are two conventional approaches explaining the construction of goal-directed processes (predetermined goals and means and the separate and arbitrary construction of goals and means). However, these approaches cannot elucidate the flexibility and diversity of actions and some characteristics of thinking. We hypothesize that the goal and means of an action are constructed jointly on the basis of the criterion of minimal construction costs and this entirely determines actions. Some ideas in favor of this mechanistic explanation of actions and objections against it are considered. The idea that the mechanism of joint construction entirely determines actions was examined in an experiment when participants were informed about the joint construction mechanism and instructed to violate its functioning by performing an action. Participants could violate the functioning of the mechanism at two levels of the action but information about one level was more explicit than about another level. It was assumed that participants would violate the functioning of the mechanism only at one level. This indicates that joint construction really determines actions because a sort of compliance between these levels was necessary to perform the action. This assumption was confirmed experimentally.